Penerapan Pembelajaran Berbasis Gamifikasi dalam Proses Pembelajaran Dasar-Dasar Teknik Ketenagalistrikan - Syafresti, Tika; Yanto, Doni Tri Putra (Jurnal Pendidikan Teknik Elektro, 2024)
This research aims to apply the application of gamification-based learning assisted by the Kahoot application to student learning outcomes in the Basics of Electrical Engineering learning process at SMK Negeri 2 Solok. The learning model used still uses the lecture method and students only listen, take notes, and wait for what the teacher orders, so this has an impact on student learning outcomes which have not been achieved optimally. Therefore, research is needed using a gamification-based learning model assisted by the Kahoot application to determine its impact on student learning outcomes. The research method used is quantitative in the form of a quasi-experiment with a pretest-posttest control group design. In this research, the instruments used include pretest and posttest questions with the final results in the form of data. The data analysis technique used in this research is the student's N-Gain Score and effect size analysis. Based on the results of data analysis and discussion, it can be concluded that the implementation of a gamification-based learning model assisted by the Kahoot application has an impact on student learning outcomes in learning the Basics of Electrical Engineering. This can be seen from the increase in student learning outcomes which have increased with the average pretest and posttest scores for the experimental class being higher than the pretest and posttest for the control class. Apart from that, analysis of the effect size results shows that the implementation of a gamification-based learning model assisted by the Kahoot application has a big influence on student learning outcomes.